Characterization and physicochemical properties analysis of konjac glucomannan: Implications for structure-properties relationships. (November 2021) - Guo, Liping; Yokoyama, Wallace; Chen, Ling; Liu, Fei; Chen, Maoshen; Zhong, Fang
Abstract: The objective of this research was to identify the structural and physicochemical factors of konjac glucomannan (KGM). Seven purified konjac flours that varied in hydration behavior and ultimate viscosity were selected and their compositional, molecular structural, and morphological properties were compared. The results suggested that the hydration rate and the development of solution viscosity were related to particle size and surface morphology of KGM particles rather than molecular structure. The particle size distribution value, D95, varied from 452.70 μm to 132.30 μm and the hydration time decreased from 90 min to 8 min, respectively. The ultimate viscosity of fully hydrated KGM solutions was not always associated with higher Mw. Our results show that lower main chain mannose to glucose (M/G) ratios led to lower viscosity and higher acetyl content exhibited higher viscosity compared to low-acetyl KGM of same Mw. The ultimate viscosity was found to be related to a greater degree of intermolecular interaction at concentrations above c*, indicated by higher n2 values, which is the slope of double logarithmic plots of 'zero-shear' specific viscosity versus degree of space occupancy (c[η]). Small angle x-ray scattering (SAXS) results suggested that molecular conformation was the key factor that affected n2, the larger hydrodynamic volume and greater intermolecular interactions that contributed to the larger n2 . The results of this research identify physicochemical factors that are necessary for rational KGM structural design as a satiating ingredient in appetite regulation and body weight management. Graphical abstract: Image 1 Highlights: KGM granule and molecular structure affect hydration rate and final viscosity. KGM is a flexible random coil hydrocolloid with rigid rod segments. Higher M/G ratio and acetyl content at same Mw increased viscosity. The ultimate viscosity was related to the intermolecular interaction at concentrations above c*.